The sustainability development dilemma in green public relations: part of CSR failure? - Muhammad Najib Husain; Erni Febrina Harahap; Youna Chatrine Bachtiar; Prety Diawati; Ernesto R.N. Santos (Faculty of Communications Science, Dr. Soetomo University, 2023)
This study explores the intricate intersection of sustainability development and green public relations (PR) within corporate social responsibility (CSR). Despite significant technological advancements in contemporary society, numerous organisations still face challenges in effectively implementing their CSR efforts, thereby impacting their social credibility. The author investigate the case of Theranos, a well-known company that exemplified failure in this domain, using VOSviewer as an analytical tool. Theranos serves as a singular case study for our analysis. Its downfall serves as a cautionary tale, highlighting the risks associated with companies that exploit sustainable development solely for their ambitious goals. Our study underscores the importance of integrating sustainable practices into company operations and viewing sustainability as an integral component rather than merely acknowledging its value superficially. This article examines moral and ethical concerns and best practices in green public relations, offering insights into the challenges organisations face in pursuing genuine sustainability and social responsibility.